Sol–gel‐adsorbent‐coated extraction needles to detect volatile compounds in spoiled fish. Issue 19 (31st August 2017) - Bang, Yejin; Hwang, Yura; Lee, Soyoung; Park, Soomi; Bae, Sunyoung
Abstract: Volatile compounds generated by fish spoilage were investigated by an inside‐needle microextraction method followed by gas chromatography with flame ionization detection and gas chromatography with mass spectrometry. The inside of a needle was coated with an adsorbent to extract the target analytes from the headspace of the sample. The examined adsorbents included β‐cyclodextrin, polystyrene resin cross‐linked with 1% divinylbenzene, and polyethylene glycol mixed with polydimethylsiloxane. The investigated volatile compounds generated by fish spoilage were acetone, 2‐butanone, 2‐butanol, 2‐propanol, dimethyl disulfide, acetic acid, and benzaldehyde. The analysis conditions for the sorption and desorption processes were optimized. Each optimized condition was validated by determining the limit of detection and the limit of quantitation from the calibration curves, as well as the recovery, reproducibility, and concentration factors. As a result, all of the fabricated needles afforded successful recoveries, above 90%, with relative standard deviations below 10%. In particular, cyclodextrin and polystyrene resin cross‐linked with 1% divinylbenzene mixed with polydimethylsiloxane show good sensitivities and concentration factors for the standard volatile compounds. The storage of fresh mackerel and salted mackerel at room temperature for 14 days caused the concentrations of dimethyl disulfide and acetic acid to significantly increase while those of acetone, 2‐butanone, 2‐propanol, and 2‐butanol changed only slightly.